2021
DOI: 10.1055/s-0040-1722718
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brain Stem Response Predictors of Hearing Outcomes after Middle Fossa Resection of Vestibular Schwannomas

Abstract: Objectives To analyze the relationship between preoperative and intraoperative auditory brain stem response (ABR) characteristics and hearing outcomes in patients with vestibular schwannomas (VS) undergoing hearing preservation (HP) surgery via a middle cranial fossa (MCF) approach. Design Prospective study. Setting Academic tertiary skull base referral center. Methods Pre- and postoperative pure-tone average (PTA) and word recognition score (WRS) were examined. Intraoperative ABR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…For intracanalicular tumors, the preservation rate was 100%, whereas only 5.3% of patients with tumors >25 mm had preserved hearing. Ren et al 183 found a hearing preservation rate of 41.7% (63 out of 151 patients). This rate was higher for intracanalicular tumors than for tumors with an APC component (57.6% vs. 29.4%, p = 0.03).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…For intracanalicular tumors, the preservation rate was 100%, whereas only 5.3% of patients with tumors >25 mm had preserved hearing. Ren et al 183 found a hearing preservation rate of 41.7% (63 out of 151 patients). This rate was higher for intracanalicular tumors than for tumors with an APC component (57.6% vs. 29.4%, p = 0.03).…”
Section: Resultsmentioning
confidence: 95%
“…The MF approach is chosen based on the surgeon’s preference, tumor size, and degree of lateral IAC involvement. 162 , 179 , 180 , 181 , 182 , 183 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the neurosurgical retrosigmoid (RS) access and destructive translabyrinthine (TL) approaches, the MCF approach is mainly used by otosurgeons for hearing-preserving microsurgery of small vestibular schwannomas (VS). The functional outcomes are good [ 5 , 6 , 7 ] and complication rates are low [ 8 ]. Other indications include vestibular neurectomy, petrous apex biopsy, cholesterol granuloma, or decompression of the internal auditory canal in patients with neurofibromatosis type II.…”
Section: Introductionmentioning
confidence: 99%